Associated Factors of Thalassemia and Thyroid Status of Thalassemic Patients (Bangladesh Medical Journal, 2025)
Thyroid dysfunction in thalassemia leads to the production of insufficient thyroid hormone which is responsible for various complications. Therefore, this study aimed to investigate the thalassemia related variables and thyroid status in the thalassemic patients. Data were collected from 138 thalassemia patients by using the questionnaire formulated after a detailed review of formerly published relevant literature. Statistical analysis was performed by using SPSS (v20, Inc., Chicago). An alpha level of 0.05 or less was considered as significant at 95% confidence interval. Around 76.1% of the patients were Hb E β-thalassemia patients including β-thalassemia major patient, β-thalassemia trait and Hb E trait and others (12.3%, 5.8%, and 2.9% respectively). History of blood transfusion had in 92% of patients. About 88% of these transfused respondents got frequent blood transfusion for the last 6 months. Iron chelator was prescribed in 58% patients either deferasirox (28.3%) or deferiprone (29.7%). Patients had the mean serum ferritin and hemoglobin level of 1682.43 (±1752.61) ng/dl and 7.81(±1.52) g/dl respectively. We found a strong correlation of transfusion dependency, interval between blood transfusions, iron chelator using and serum ferritin control with the thyroid status. The study also revealed that non-transfusion dependent and iron chelator independent respondents were less likely to develop hypothyroidism (ꭓ² = 9.81; p = 0.002 and ꭓ² = 8.424; p = 0.004, respectively). Hypothyroidism was more common in respondents with frequent blood transfusion compared with that of others (ꭓ² = 11.276; p = 0.003) and in respondent with bad control of serum ferritin than the respondents with good control (ꭓ² = 13.929; p < 0.001). The present study explored various thalassemia related factors including transfusion dependency, interval between blood transfusions, iron chelator using and serum ferritin control with the thyroid status. Further study is required to support our findings.Bangladesh Med J. 2024 May; 53(2): 19-25